Design of digital charger based on AVR microcontroller. Issue 1 (October 2020) - Qu, Weidong; Yu, Lijie
Abstract: Most of the rechargeable batteries in the equipment can only use a dedicated charger, and it is impossible to determine the charging parameters and the remaining charging time. In order to solve this problem, we design a digital charger, single-chip microcomputer control as the core, to real time control of rechargeable batteries, can real time collection and rechargeable battery voltage, current, the rest of the parameters such as charging time, can also by serial port and PC communication, and through the display device according to the necessary information to users.